Sensitive, simultaneous quantitation of two unlabeled DNA targets using a magnetic nanoparticle-enzyme sandwich assay - Yue Zhang (2018)
We report herein the development of a simple, sensitive colorimetric magnetic nanoparticle (MNP)-enzyme-based DNA sandwich assay that is suitable for simultaneous, label-free quantitation of two DNA targets down to 50 fM level. It can also effectively discriminate single-nucleotide polymorphisms (SNPs) in genes associated with human cancers (KRAS codon 12/13 SNPs). This assay uses a pair of specific DNA probes, one being covalently conjugated to an MNP for target capture and the other being linked to an enzyme for signal amplification, to sandwich a DNA target, allowing for convenient magnetic separation and subsequent efficient enzymatic signal amplification for high sensitivity. Careful optimization of the MNP surfaces and assay conditions greatly reduced the background, allowing for sensitive, specific detection of as little as 5 amol (50 fM in 100 μL) of target DNA. Moreover, this sensor is robust, it can effectively discriminate cancer-specific SNPs against the wild-type noncancer target, and it works efficiently in 10% human serum. Furthermore, this sensor can simultaneously quantitate two different DNA targets by using two pairs of unique capture- and signal-DNA probes specific for each target. This general, simple, and sensitive DNA sensor appears to be well-suited for a wide range of genetics-based biosensing and diagnostic applications. © 2013 American Chemical Society.